Correlation of lineaments to ground water inflows in the MWRA tunnel - Stephen B Mabee; Curry, Patrick J.; Hardcastle, Kenneth C. (Abstracts with Programs - Geological Society of America, 2001)
Lineaments derived from three image types (1:80,000 black and white (BW), 1:58,000 color infrared (CIR), and 1:250,000 side-looking airborne radar (SLAR)) were compared to water-bearing features within a 9.6 km section of tunnel being constructed through foliated crystalline metamorphic bedrock in a glaciated region of eastern Massachusetts. Lineaments drawn by three observers during two independent trials (N = 9137) were reduced to three sets (one per image type) of coincident lineaments (N = 794). Thirty-five coincident lineaments crossed the tunnel. Nineteen discrete flow zones, each producing less than or equal to 19 L/min, were identified in the tunnel and used to quantify the reliability of lineament analysis as a method of predicting water-bearing features in glaciated metamorphic rocks. Thirteen (68%) of the flow zones correlate with coincident lineaments, six zones correlate with more than one image type, and one zone correlates with all three image types. Overall, it is difficult to distinguish lineaments that will be successful in predicting water-bearing zones from those that will be unsuccessful without considering other corroborating evidence. Most of the observed flow (80%) correlates with northwest-trending coincident lineaments. However, the majority of the flow (67%) associated with these lineaments is produced from structures that strike to the north or northeast. In addition, only fifteen of the thirty-five coincident lineaments correlate with the flow zones indicating that twenty lineaments are not associated with any appreciable flow. Six flow zones are undetected by the lineament analysis. In this study, BW lineaments are able distinguish high-yield through-going structures (at the 90% confidence level) with greater reliability than the SLAR or CIR lineaments. However, linking bedrock type, overburden type, topographic position, and proximity to surface water bodies with lineament analysis improves the predictive capability of the lineament method.
Keywords: #StaffPubs; black and white; construction; correlation; eastern Massachusetts; Engineering geology 30; experimental studies; flow rates; geophysical methods; ground water; infrared methods; lineaments; mapping; massachusetts; metamorphic rocks; methods; movement; photogeology; radar methods; remote sensing; SLAR; tectonics; tunnels; United States

Deep geothermal potential of New England granitoids; the Fall River Pluton, southeastern Massachusetts - Goodhue, Nathaniel; Koteas, G. Christopher; John Michael Rhodes; Stephen B Mabee (Abstracts with Programs - Geological Society of America, 2011)
Devonian-aged plutonic rocks that are interpreted to be part of the Fall River pluton, along the southern edge of the Narragansett Basin, appear to have potential as a source of deep geothermal energy. The Narragansett Basin covers a approximately 1500 Km (super 2) area in southern Massachusetts and is dominated by complexly deformed and metamorphosed, Pennsylvanian-aged, fluvial and alluvial deposits. A northeast-striking series of brittle faults and discrete shear zones define the southern margin of the basin. Preliminary modeling of igneous and gneissic fabrics from outcrops along the southern edge of the basin show that the granite dips predominantly north, northeast. This pattern suggests that granitoids along the southern edge of the basin continue beneath the Narragansett Basin and correlate with granitoids exposed to the north. Regional joint sets in the Fall River pluton can be grouped into three dominant clusters at 350 degrees , 90 degrees , and 250 degrees based upon 86 field measurements. Low-angle sheeting joints are also common and suggest interconnected fracture networks at depth. Preliminary geochemistry from the Fall River pluton suggests that feldspars and accessory minerals contain the appropriate concentrations of heat producing elements, primarily U, Th, and K, to be a reasonable geothermal resource. K (sub 2) O values range from 2.4 to 5.0 weight percent. U and Th values (in ppm) range from 0.9 to 6.2 and 2.9 to 30.1 respectively. Assuming a relatively consistent composition at depth, a density of 2.6 kg/m (super 3) , and a thermal conductivity of 2.9 W/m degrees C, initial temperature modeling suggests average temperatures of 81 degrees C at depths of 5 kilometers and 93 degrees C at depths of 6 kilometers. Temperature estimates increase to approximately 150 degrees C and approximately 170 degrees C respectively when a two kilometer thick sediment package is modeled overlying the granitoids. The goal of current and future work is to improve assumptions about compositional uniformity as well as the regional position of granitoids at depth. At the conclusion of this work we hope to develop a protocol for studying geothermal potential of buried granitoids in New England in the absence of reliable drill-hole data. Preliminary estimates from this project suggest that basins underlain by granitoids of compositions similar to that of the Fall River pluton have reasonable potential as a deep geothermal resource.
Keywords: #StaffPubs; depth; Economic geology, geology of energy sources 29A; Fall River Pluton; geochemistry; geothermal energy; gneisses; granites; Igneous and metamorphic petrology 05A; igneous rocks; intrusions; massachusetts; metamorphic rocks; plutonic rocks; plutons; southeastern Massachusetts; United States

Factors influencing groundwater inflows in a newly constructed cross-strike tunnel, eastern Massachusetts; 1, Lineaments and subsurface structures - Curry, Patrick J.; Hardcastle, Kenneth C.; Stephen B Mabee; Williams, Katherine W. (Abstracts with Programs - Geological Society of America, 1999)
Lineaments derived from three platforms; 1:250,000 Side-Looking Airborne Radar (SLAR) images, 1:58,000 Color Infrared (CIR) and 1:80,000 Black and White aerial photographs (BW), were compared to water bearing structures (n = 99) within a 9 km, 70 to 90 meter deep, east-west tunnel being constructed in eastern Massachusetts. Lineaments were drawn by three observers during two independent trials to produce 18 sets of lineaments (n = 9137) covering approximately 1,000 km (super 2) centered over the tunnel. All lineaments for each platform were compared. Three or more overlapping lineaments (azimuths within 5 degrees and within 1 mm at the scale of the imagery) define a single coincident lineament. This analysis generated three sets of coincident lineaments (n = 794), of these 37 cross the tunnel. Buffers were placed around the coincident lineaments at a distance of 1 mm from the center of the lineament at the scale of the platform (e.g. 250 m for the SLAR image). The Mann-Whitney U test was used to determine if the median flow from all tunnel structures which underlie the lineament buffer zones is significantly greater than that of all structures outside of the buffer zones. Results indicate that median flow (11,000 l/day) from structures located within the buffer zones of the BW are significantly greater at the 90% confidence level than the median flow (5,500 l/day) of structures located outside the buffer zones. No significant differences in flow were found for the other two platforms. Subsurface structures that parallel coincident lineaments (all platforms) and occur within the buffer zones have higher median flow (10,500 l/day) than those structures outside the buffer zones (6,600 l/day). However, this difference is significant at the 70% confidence level. These results suggest that, in some instances, a thorough lineament analysis can predict water-bearing subsurface structures in poorly exposed, glaciated, metamorphic terrain that has a high degree of suburban development.
Keywords: #StaffPubs; BEDROCK; eastern Massachusetts; fractures; geophysical surveys; ground water; Hydrogeology 21; lineaments; massachusetts; metamorphic rocks; movement; New England; remote sensing; SLAR; strike; surveys; tectonics; tunnels; United States

Lineaments; their value in assessing regional groundwater availability and quality in bedrock aquifers of glaciated metamorphic terrains; a case study - Stephen B Mabee (Abstracts with Programs - Geological Society of America, 1993)
Keywords: #StaffPubs; amphibolite; aquifers; Atlantic Coastal Plain; BEDROCK; central Maine; fractures; Georgetown Maine; ground water; hydraulic conductivity; hydrogeology; lineaments; Maine; metamorphic rocks; structural controls; United States; water quality

Factors influencing well productivity in glaciated metamorphic rocks - Stephen B Mabee (Ground Water, 1999)
Keywords: #StaffPubs; aquifers; BEDROCK; controls; depth; drinking water; fractures; Georgetown Island; glacial environment; ground water; Hydrogeology 21; Maine; metamorphic rocks; porosity; surface water; thickness; topography; transmissivity; United States; water wells